O PROCESSO DE ELABORAÇÃO DA BNCC E OS ITINERÁRIOS FORMATIVOS: IMPACTOS PARA O CURRÍCULO DO ENSINO MÉDIO - Caroline Rocha (2024)
This work is part of the context of the Master's program in Education at the Federal University of Mato Grosso do Sul (UFMS), Três Lagoas Campus, in the research line of Teacher Training and Public Policies. The research aimed to investigate the implications of neoliberal ideas present in the National Common Curricular Base (BNCC) and in the High School Reform (EM), highlighting the points of convergence that evidence a neoliberal orientation in the configuration of the Brazilian educational system. In the BNCC, neoliberal premises are observed in the pursuit of curricular homogenization, centered on the standardization of competencies and skills. The emphasis on preparing students for the job market, to the detriment of a comprehensive education, suggests a utilitarian view of education, while the emphasis on quantitative indicators can promote the commodification of education, encouraging competition between institutions. Similarly, the EM Reform also reflects a neoliberal approach, aiming to adapt education to market demands. The methodology is structured through bibliographic and documentary research. The intention is to argue and analyze school education framed in the reform driven by neoliberal policies present in the Brazilian state, mainly through the BNCC and the curriculum for EM. We critically analyze the relationship between the BNCC and the EM Reform in the context of neoliberal policy. The BNCC, by defining common curricular guidelines, and the EM reform, by introducing greater flexibility, highlight a complex interaction between the pursuit of standardization and the need to adapt to contemporary demands. The analysis emphasizes challenges in implementation and highlights the duality between uniformity and flexibility, especially regarding equity. Considering the neoliberal context, this dissertation also examines the impact of these policies on education, highlighting their influence on labor relations and curricular policies. Ultimately, this study emphasizes the importance of continuous critical analysis to shape future adjustments and ensure equity in the Brazilian educational system.